Celastrol Suppresses Glioma Vasculogenic Mimicry Formation and Angiogenesis by Blocking the PI3K/Akt/mTOR Signaling Pathway - Zhu, Yingjun (Front Pharmacol, 2020)
Angiogenesis and vasculogenic mimicry (VM) are thought to be the predominant processes ensuring tumor blood supply during the growth and metastasis of glioblastoma (GBM). Celastrol has potential anti-glioma effects, however the mechanisms underlying these effects remain unclarified. Recent studies have shown that the PI3K/Akt/mTOR signaling pathway is closely related to angiogenesis and VM formation. In the present study, we have demonstrated, for the first time, that celastrol eliminated VM formation by blocking this signaling pathway in glioma cells. By the treatment of celastrol, tumor growth was suppressed, tight junction and basal lamina structures in tumor microvasculature were disarranged in U87 glioma orthotopic xenografts in nude mice. Periodic acid Schiff (PAS)-CD31 staining revealed that celastrol inhibited both VM and angiogenesis in tumor tissues. Additionally, celastrol reduced the expression levels of the angiogenesis-related proteins CD31, vascular endothelial growth factor receptor (VEGFR) 2, angiopoietin (Ang) 2 and VEGFA, VM-related proteins ephrin type-A receptor (EphA) 2, and vascular endothelial (VE)-cadherin. Hypoxia inducible factor (HIF)-1α, phosphorylated PI3K, Akt, and mTOR were also downregulated by treatment with celastrol. In vitro, we further demonstrated that celastrol inhibited the growth, migration, and invasion of U87 and U251 cells, disrupted VM formation, and blocked the activity of PI3K, Akt, and mTOR. Collectively, our data suggest that celastrol inhibits VM formation and angiogenesis likely by regulating the PI3K/Akt/mTOR signaling pathway.